RESPON PERTUMBUHAN DAN PRODUKSI TANAMAN KACANG HIJAU (Vigna radiata L) PADA BERBAGAI KONSENTRASI HORMON GA3 DAN DOSIS PUPUK NPK - Teuku Sarwanidas; Mita Setyowati (Jurnal Agrotek Lestari, 2018)
This study aims to determine the response of growth and production of green beans to various concentrations of the hormone GA3 and the dosage of NPK fertilizer and the real or not the interaction of both factors. The experimental experiments used in the study were Randomized Block Design (RAK) 3 x 3 factorial pattern with 3 replications. The factors studied include the concentration of gibberellin (G) consisting of 3 levels, namely: 50 ppm (0.05 ml / liter), 100 ppm (0.10 ml / liter) and 150 ppm (0.15 ml / liter). The compound dose of NPK compound fertilizer consisted of 3 levels: 250 kg ha-1 (1.50 g / polybag), 300 kg ha-1 (1.80 g / polybag) and 350 kg ha-1 (2.19 g / polybags). The experiment was conducted in Experimental Garden of West Aceh Food and West Aceh crops, from October to January 2016. The results showed that gibberellin concentration significantly affected the number of productive branches of 56 HST and no significant effect on plant height and stem base diameter 18, 25, 32 and 39 HST, number of pods and dry seed weight aged 56, 59 and 63 HST and weight of 100 dry beans. The dosage of NPK fertilizer had significant effect on plant height and stem diameter of 32 and 39 HST, dry seed weight and no significant effect on plant height and stem diameter of 18 and 25 HST, number of productive branches 56 DAP, number of pods age 56, 59 and 63 DAP and weighing 100 dry seeds. Keywords: hormone Giberelin GA3, NPK fertilizer, green bean plant